2018
DOI: 10.1111/hsc.12546
|View full text |Cite
|
Sign up to set email alerts
|

Assessing care-giving demands, resources and costs of family/friend caregivers for persons with mental health disorders: A scoping review

Abstract: As mental health (MH) care has shifted from institutional settings to the community, families and friends are responsible for providing the majority of the care at home. The substantial literature on the adverse effects experienced by caregivers has focused mainly on psychological morbidity. Less attention has been paid to how caregivers for persons with MH disorders interact with larger social systems and the impacts of factors such as financial strain, lost time from leisure activities, and the availability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 103 publications
(196 reference statements)
2
7
0
Order By: Relevance
“…The financial burden of caring for someone with mental illness was commonly reported in care‐giving studies (Lin et al., 2018) which was also found in this study (Theme 3, Subtheme 2). Although there are some financial assistance schemes for people with mental illness in Singapore, there are no dedicated schemes to help carers financially.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The financial burden of caring for someone with mental illness was commonly reported in care‐giving studies (Lin et al., 2018) which was also found in this study (Theme 3, Subtheme 2). Although there are some financial assistance schemes for people with mental illness in Singapore, there are no dedicated schemes to help carers financially.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, findings of this study suggest that some carers in Singapore may lack adequate information and are not involved actively in the treatment discussion and planning. Given that support from families is crucial in the recovery process of people with mental illness, failure to involve them will The financial burden of caring for someone with mental illness was commonly reported in care-giving studies (Lin et al, 2018) which was also found in this study (Theme 3 The need for respite care of people with mental illness was also reported by carers (Theme 3, Subtheme 3). This is not a new finding as numerous care-giving studies reported this need as well (Jardim & Pakenham, 2010).…”
Section: Discussionsupporting
confidence: 68%
“…Taking a conservation of resources perspective, we argue that behavioral health services and other family supports may increase caregiver participation in the paid labor force, allowing for the accumulation and protection of resources. Additional research is needed to assess the impact of specialized services and supports for youth with mental health challenges on caregiver employment [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although caregiving helps decrease patient burden, caregivers themselves can be negatively affected (Del-Pino-Casado et al, 2021;Liu et al, 2020;Pinquart & Sorensen, 2003;Schulz & Beach, 1999). Caregivers may experience poorer physical and mental health, diminished life expectancy, financial strain, loss of productivity, inability to work, and social isolation (Adelman et al, 2014;Greenwood et al, 2018;Lin et al, 2018;Pinquart & Sorensen, 2003;Schulz & Beach, 1999).…”
Section: Introductionmentioning
confidence: 99%